Learning to Shift Power and Center Community Voices in International Development Work - Jill LaLonde; Sheku Mohamed Gassimu Jr. (Interdisciplinary Journal of Partnership Studies, 2023)
International development has long been dominated by primarily white-led, Global North organizations. These organizations are raising money in the Global North and doing work in the Global South, with the intended benefit to less economically developed communities. In recent years, there has been a significant increase in activism and calls by organizations in both the Global North and South for localization of development, humanitarian aid, and peacebuilding efforts in an attempt to address unequal North-South power dynamics. Since 2006, OneVillage Partners has worked to address multidimensional poverty in Sierra Leone by investing in individuals and communities to help them address their own challenges, providing targeted project facilitation and monetary support for communities to lead their own development, and connecting individuals and leaders with one another across communities to amplify their collective voices and actions for broader impact. Beginning in 2020, OneVillage Partners increased its commitment to “decolonize” their work and more fully shift power to local people in Sierra Leone. This article will provide context on the changing nature of the international development industry and outline steps OneVillage Partners has taken to operationalize the localization narrative, challenges they have encountered, and ideas for the future.